Casein glycomacropeptide pH-dependent self-assembly and cold gelation - Farias, M. E. (2010)
The self-assembly of 3–5% (w/w) casein glycomacropeptide (CMP) at room temperature and pH 3–6.5 was determined by dynamic light scattering immediately after pH adjustment and over time, and the rate of gelation at a concentration of 3–10% (w/w) was determined by a tilting test. The intensity particle size distribution at pH 6.5 was multimodal with a predominant peak at 2.3 nm. The hydrodynamic diameter increased when decreasing the pH from 6.5 to 3. CMP solutions at a pH below 4.5 showed time-dependent self-assembly at room temperature, which led over time to gelation. The minimum concentration for cold gelation depended on pH. Below pH 4, CMP gelled even at low concentrations (3%, w/w). The pH-reversibility of self-assembled CMP was not total, showing that hydrophobically bound dimers, once formed, are stable to pH changes. A model to explain CMP self-assembly and the formation of a network-like structure (gel) at room temperature is proposed.